Washout effect in rabbit brain: in-beam PET measurements using 10C, 11C and 15O ion beams. (2nd March 2018) - Toramatsu, Chie; Yoshida, Eiji; Wakizaka, Hidekazu; Mohammadi, Akram; Ikoma, Yoko; Tashima, Hideaki; Nishikido, Fumihiko; Kitagawa, Atsushi; Karasawa, Kumiko; Hirano, Yoshiyuki; Yamaya, Taiga
Abstract: In particle therapy, in-beam positron emission tomography (PET) is expected to enable in situ noninvasive confirmation of the treatment delivery. For accurate range and dose verification or three-dimensional (3D) volume imaging, however, correction of the biological washout effect in a living body is necessary. In this study, we measured the washout rate in a rabbit brain using the recently developed technology for oxygen beam radiation as well as carbon ion beam radiation. To measure components of washout, three radionuclides, 10 C, 11 C and 15 O, which were generated as secondary beams in the Heavy Ion Medical Accelerator in Chiba (HIMAC), were irradiated on the rabbit brain under two conditions, live and dead. In-beam data were acquired by our whole body dual-ring OpenPET, which enables 3D in-beam imaging. Regions of interests (ROIs) were set as a 3D positron distribution and the time activity curves (TACs) of the irradiated field were acquired. We obtained the washout rate for those conditions based on multiple component model analysis. A difference between washout speed in 11 C ions and the 15 O ions was observed. The observed medium and slow biological decay rates of 11 C ions in rabbit brain were 0.30 min −1 and 0.004 min −1, respectively. Those values were consistent with the previous rabbit study results acquired by other imaging modalities, such as the pair of positron cameras or our single-ring small animal OpenPET prototype. The observed medium and slow biological decay rates of 15 O ions were 0.72 min −1 and 0.024 min −1, respectively, which were faster than those of the 11 C ion. Also, the medium biological decay rate of 15 O ions was close to the washout rate in cerebral blood flow (CBF) measurements by dynamic PET with 15 O-labeled water. These results should help to establish an accurate washout correction model.